Pengaruh Kinerja Account Representative, Self Assessment System, dan Pemeriksaan Pajak Terhadap Tingkat Kepatuhan Wajib Pajak - Suyanto .; Andri Setiawan (Universitas Muhammadiyah Ponorogo, 2017)
This research is aimed to examine the effect of the performance of AR, self- assessment system, and the tax audit of the individual taxpayer compliance. This research was conducted in the Tax Office (KPP) Pratama Yogyakarta. The data used are primary data on the results of questionnaire 104 respondents and data that can be processed as many as 99 questionnaire. The sampling method using a convenience sampling and data analysis technique used is multiple linear regression techniques. This research findings show that performance of AR, self-assessment system, and the tax audit in partially and simultaneous have had a positive effect on compliance of individual taxpayers